Optimizing Basic Competition Selection Book Distribution Costs Using the North West Corner and Modified Distribution Methods - Alfian Putra Ardana; Dimas Anggrawan Hadinata; Nuzla Af'idatur Robbaniyyah (University of Mataram, 2026)
High distribution costs represent a major challenge in delivering Basic Competency Selection (BCS) books across various regions in Indonesia, primarily due to inefficient allocation of shipments. This study aims to optimize distribution costs by applying transportation methods through a combination of the North West Corner (NWC) and Modified Distribution (MODI) methods. The data used are quantitative, obtained through direct interviews with distributors, including transportation costs, supply capacities from each source, and demand at each destination. The NWC method is employed to generate an initial feasible solution, which is then improved using the MODI method to achieve an optimal solution. The results indicate that the initial distribution cost of Rp4,533,000 can be reduced to Rp3,651,000 after optimization, reflecting a cost efficiency of 19.46%. Therefore, the combination of NWC and MODI methods is proven to be effective in minimizing distribution costs and can serve as a practical decision-support tool in logistics planning, particularly in educational material distribution.